THE EFFECT OF NICKEL ELECTROPLATING ON THE SURFACE HARDNESS OF LOW CARBON STEEL - Salman; Wiranata, Ardi; Sinarep; Dwi Setyawan, Paryanto (Energy, Materials and Product Design, 2022)
Electroplating on steel is basically done with the aim of protecting the steel surface from corrosion attack. However, it is necessary to know the quality surface hardness of steel that has undergone electroplating. This research is determining the electroplating time and the best anode and cathode distance to surface hardness in the nickel electroplating process on low carbon steel. The method was done by placing the specimen into a electrolyte solution. Then the hardness test was carried out on the specimen. The results shown that the ST-37 steel coating with nickel with a variation of the plating time of 12 minutes and the distance between the anode and cathode of 150mm,has highest hardness number of 246.7kg/mm2. By ANOVA analysis the coating time greatly affects the surface hardness.